PENGARUH PERILAKU AKUNTANSI DAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN PADA PT. REKAYASA INDUSTRI INDUSTRI SAMUR PROYEK - Haironi, Rita; Hamta, Firdaus; Santoso, Cahyo Budi (MEASUREMENT : Jurnal Program Studi Akuntansi, 2015)
Influence the behavior of the system of accounting and accounting inforrmasi to the quality of the financial statements. at PT. Rekayasa Industry Samur Project. With the formulation of the problem Is there any influence between the behavior of the system of accounting and accounting information on the quality of the financial statements. Research purposes in accordance with the formulation of the problem is to determine whether there was an effect of the behavior of the system of accounting and accounting information on the quality of the financial statements at PT Rekayasa Industry Samur Project.The results of this study: Coefficient table value of t test obtained t value 0956 and sig. for 0342 0.05. And thus, accounting behavior does not significantly influence the quality of financial statements at PT. Rekayasa Industri Project Samur. From the coefficient table t test, sig. for 0132 from 0:05 So thus accounting information system does not significantly influence the quality of financial statement at PT. Rekayasa Industri Project Samur. From the model summary table, showing r-square 0656 or 65.6%. Simultaneously it means there is a relationship between behavior or contribution accounting and accounting information system on the quality of the financial statements at PT Rekayasa Indusri Samur Project of 65.6%, and 34.4% in the contribution by another variable or variables that are not observed.